THE IMPACT OF INDIRECT FOREIGN INVESTMENT ON INDICATORS OF FINANCIAL STABILITY IN IRAQ - Kadhim Saad Abdul Ridha Al-Araji; Mohammed Naji Mohammed Al-Zubaidi; Shaimaa Abdel Hadi Hussein Al Sharifi (Scholar Express Journals, 2022)
Indirect foreign investment is one of the investments directed to the purchase of securities issued by public or private bodies of the state and the important role played by indirect foreign investment for all economic sectors by attracting savings and transferring them to invest in securities, whether shares or bonds, and what has an impact on achieving Financial stability and highlighting the positive role of Iraqi banks by enhancing financial stability during financial crises, as the research reached a statement about the role of foreign indirect investment in the extent of achieving financial stability and enhancing its position in Iraqi banks and showing indicators of financial stability, the research recommended opening the financial markets to become more liberal and be able to attract indirect foreign investment and benefit from the experiences of other countries to achieve financial stability
Keywords: Indirect foreign investment; savings and transferring; experiences; countries